Peran Tim PPK Ormawa BEM FK UPR dalam Peningkatan Pengetahuan Anemia dan Skrining Kadar Hemoglobin Remaja Putri MTS dan MA Darul Ulum, Palangka Raya - Novita Wulandari; Sazly, Muhammad Revo Andaluzio; Ananda, Desire Reskia; Prasetyo, Dafiq Amral; Daniel Yuantara; Darsana, I Nyoman; Adinda, Naya Safira; Murti, Tabita Hayu Panca; Vany, Destia; Anna; Sihombing, Katrin; Budi Aulyansyah Ahmad Trisna; A.Irwin Putra Pangestin; Ni Nyoman Sri Yuliani (LPPM Universitas Palangka Raya, 2024)
Stunting is a malnutrition condition in toddlers who have less height compared to children their age, and anemia is one of the main causes. Adolescent girls who experience anemia are at high risk of developing it until pregnancy, negatively impacting fetal development and causing Low Birth Weight (BBLR) or prematurity. The